2021
DOI: 10.1155/2021/5165115
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of Machine Learning Model Based on Text Mining and Ranking of Meituan Merchants

Abstract: In the Web 2.0 era, the problem of uneven quality and overload of online reviews is very serious, and the cognitive cost of obtaining valuable content from them is getting higher and higher. This paper explores an effective solution to address comment overload by means of information recommendation in order to improve the utilization of online information and information service quality. This paper proposes a review ranking recommendation scheme that focuses on the information quality of reviews and places mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Theoretically, the notion of psychological distance is appropriate for illuminating review recipients' travel intentions related to online destination reviews. Although many studies have verified this hypothesis, some studies have found that the moderating role of psychological distance is absent in certain situations (Shin et al, 2019;Tang et al, 2021). Therefore, this study appropriately expands the dimensions of psychological distance and further examines the interaction effects of review content characteristics and psychological distances on travel intention.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Theoretically, the notion of psychological distance is appropriate for illuminating review recipients' travel intentions related to online destination reviews. Although many studies have verified this hypothesis, some studies have found that the moderating role of psychological distance is absent in certain situations (Shin et al, 2019;Tang et al, 2021). Therefore, this study appropriately expands the dimensions of psychological distance and further examines the interaction effects of review content characteristics and psychological distances on travel intention.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, it is of great significance to identify valuable reviews and effectively use them to stimulate potential AJIM 76,1 42 tourists' travel intentions. Although a considerable amount of literature has provided insights into the impact of online reviews on tourists' decision-making in quantity (Zeng et al, 2020), timeliness (Li et al, 2019), rating (Kim et al, 2020), textual length (Zinko et al, 2020) and usefulness vote (Tang et al, 2021), it is relatively simple to examine the impact of quantitative characteristics of potential tourists' online reviews.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations